2018
DOI: 10.1016/j.cub.2018.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Coin Tossing Explains the Activity of Opposing Microtubule Motors on Phagosomes

Abstract: SummaryHow the opposing activity of kinesin and dynein motors generates polarized distribution of organelles inside cells is poorly understood and hotly debated [1, 2]. Possible explanations include stochastic mechanical competition [3, 4], coordinated regulation by motor-associated proteins [5, 6, 7], mechanical activation of motors [8], and lipid-induced organization [9]. Here, we address this question by using phagocytosed latex beads to generate early phagosomes (EPs) that move bidirectionally along microt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 44 publications
(115 reference statements)
2
24
0
Order By: Relevance
“…Together, our results point out a mechanism of heterogeneity generation that is for the most part stochastic and might be a general mechanism for generating heterogeneity in dividing cells. The possibility that particulate material is unevenly distributed in telophase into two nascent daughter cells has been proposed for other organelles and in other cellular systems (Bergeland et al, 2001;Carlton et al, 2020;Sanghavi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, our results point out a mechanism of heterogeneity generation that is for the most part stochastic and might be a general mechanism for generating heterogeneity in dividing cells. The possibility that particulate material is unevenly distributed in telophase into two nascent daughter cells has been proposed for other organelles and in other cellular systems (Bergeland et al, 2001;Carlton et al, 2020;Sanghavi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Together, our results point out a mechanism of heterogeneity generation that is for the most part stochastic and might be a general mechanism for generating heterogeneity in dividing cells. The possibility that particulate material is unevenly distributed in telophase into two nascent daughter cells has been proposed for other organelles and in other cellular systems ( Bergeland et al, 2001 ; Carlton et al, 2020 ; Sanghavi et al, 2018 ). Indeed, in MDCK cells, microscopy analysis and mathematical modeling based on the laws of probability suggested that endosome/lysosome partitioning between daughter cells is stochastic ( Bergeland et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…This work adds to a growing body of evidence that, first, the position of motors on the cargo (whether free or not) impacts transport [4,24]; second, that mobility on the cargo surface further influences transport [8,9,17,18,25]; and, third, that there are significant differences in the arrangement of motors on cargo in cells [3,18], for example via changes to lipid content [26,27]. The closest direct experimental study related to our work is by the Xu Lab [9].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…The possibility that particulate material is unevenly distributed in telophase into two nascent daughter cells has been proposed for other organelles and in other cellular systems (Bergeland et al, 2001; Carlton et al, 2020; Sanghavi et al, 2018). Indeed, in MDCK cells, microscopy analysis and mathematical modelling based on the laws of probability suggested that endosomes/lysosomes partitioning between daughter cells is stochastic (Bergeland et al, 2001).…”
Section: Discussionmentioning
confidence: 99%